Zolmitriptan Nasal Spray in the Acute Treatment of Cluster Headache: A Meta-Analysis of Two Studies - Hedlund, Cecilia; Rapoport, Alan M.; Dodick, David W.; Goadsby, Peter J. (Headache, 2009)
Objective.— To conduct an individual subject meta‐analysis of available controlled studies of zolmitriptan nasal spray in the acute treatment of cluster headache. Background.— Two double‐blind, placebo‐controlled, randomized, crossover studies of zolmitriptan nasal spray in the acute treatment of cluster headache, with similar patient populations, protocol designs, doses, and clinical endpoints have been published. Methods.— In both double‐blind studies, each patient was to treat 3 attacks, 1 with placebo, 1 with zolmitriptan 5 mg, and 1 with zolmitriptan 10 mg in a randomized, crossover manner. Headache intensity was rated on a 5‐point scale (none to very severe). The primary endpoint was headache relief at 30 minutes post dose: reduction from moderate, severe, or very severe pain to mild or none. A multilevel, random‐effects, logistic regression model was used to analyze the data. Results.— A total of 121 patients (100 male; 64.5% with episodic cluster headache) provided efficacy data for at least 1 attack. Zolmitriptan 5 mg and 10 mg were significantly more effective at providing headache relief at 30 minutes post treatment than placebo (odds ratio 3.48; 95% confidence interval 1.49‐8.10 and odds ratio 8.68; 95% confidence interval: 3.35‐22.5, respectively). For episodic cluster headache, response rates were 35.6%, 51.7%, and 73.7% for placebo, zolmitriptan 5 mg (odds ratio 2.5; P = .06 vs placebo), and 10 mg (odds ratio 9.9; P < .001 vs placebo), respectively. For chronic cluster headache, response rates were 17.2%, 41.9%, and 40.7% for placebo, zolmitriptan 5 mg (odds ratio 8.1; P = .035), and 10 mg (odds ratio 7.6; P = .046), respectively. Zolmitriptan was well tolerated in both studies with no serious adverse events reported. Conclusion.— Zolmitriptan nasal spray at a dose of 5 mg and 10 mg is efficacious in the acute treatment of episodic and chronic cluster headache.